(3GdJWhjQ GdJfXjej hGdGOGQjs - (3GdScGQfI(B, (3HdGd Ndas ((3YeGfs (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYIs, 2022)
(3jbOe cJGH (B"(3GdJWhjQ GdJfXjej hGdEOGQj(B" (3ddcGJH HdGd Nda GdScGQfI OQGSI TGedI hTNUjI YejbI aj YGde GdJZjjQ GdJfXjej(B. (3jZWj GdcJGH LhGfH eJYOOI ef GdJWhjQ GdJfXjej hGdEOGQj, HOkAG ef GdeaGgje GdCSGSjI hUhdkG Edi GdJWHjbGJ GdYedjI(B. (3jfGbT GdcJGH CgejI GdJZjjQ GdJfXjej aj JYRjR caGAI haYGdjI GdefXeGJ, hjSJYQV eLehYI hGSYI ef GdCOhGJ hGdeaGgje GdJj jecf GSJNOGegG dJMbjb gPG GdgOa(B. (3jTed Pdc OQGSI GdKbGaI GdJfXjejI, hHfGA aQb GdYed GdaYGdI, hJWhjQ GdbjGOI, hJMSjf YedjGJ GJNGP GdbQGQ(B. (3ceG jJfGhd GdcJGH GdJMOjGJ GdJj JhGLg YedjI GdJZjjQ GdJfXjej, hcjajI GdJYGed eYgG hGdJZdH YdjgG(B. (3HGdEVGaI Edi Pdc, jbOe GdcJGH OQGSGJ MGdI hGbYjI JhVM JWHjb eaGgje GdJWhjQ GdJfXjej aj eNJda GdbWGYGJ(B. (3HTcd YGe, jYJHQ gPG GdcJGH eQLYkG bjekG ddegJejf HJWhjQ COGA efXeGJge hJMbjb GdJejR(B. (3HGNJUGQ, jbOe GdcJGH EWGkQG fXQkjG hYedkjG ddJacjQ aj GdJZjjQ GdJfXjej, hjhaQ ddbGQF eLehYI ef GdCOhGJ hGdCacGQ GdJj jecf JWHjbgG dJMbjb JMhd EjLGHj aj GdefXeGJ(B.s
Keywords: (3GdJWhjQ GdJfXjejs; (3GdJfXje GdGOGQjs